Embryonic Temperature Programs Phenotype in Reptiles - Singh, Sunil Kumar; Das, Debojyoti; Rhen, Turk (Frontiers in Physiology, 2020)
Reptiles are critically affected by temperature throughout their lifespan, but especially so during early development. Temperature-induced changes in phenotype are a specific example of a broader phenomenon called phenotypic plasticity in which a single individual is able to develop different phenotypes when exposed to different environments. With climate change occurring at an unprecedented rate, it is important to study temperature effects on reptiles. For example, the potential impact of global warming is especially pronounced in species with temperature-dependent sex determination (TSD) because temperature has a direct effect on a key phenotypic (sex) and demographic (population sex ratios) trait. Reptiles with TSD also serve as models for studying temperature effects on the development of other traits that display continuous variation. Temperature directly influences metabolic and developmental rate of embryos and can have permanent effects on phenotype that last beyond the embryonic period. For instance, incubation temperature programs post-hatching hormone production and growth physiology, which can profoundly influence fitness. Here, we review current knowledge of temperature effects on phenotypic and developmental plasticity in reptiles. First, we examine the direct effect of temperature on biophysical processes, the concept of thermal performance curves, and the process of thermal acclimation. After discussing these reversible temperature effects, we focus the bulk of the review on developmental programming of phenotype by temperature during embryogenesis (i.e., permanent developmental effects). We focus on oviparous species because eggs are especially susceptible to changes in ambient temperature. We then discuss recent work probing the role of epigenetic mechanisms in mediating temperature effects on phenotype. Based on phenotypic effects of temperature, we return to the potential impact of global warming on reptiles. Finally, we highlight key areas for future research, including the identification of temperature sensors and assessment of genetic variation for thermosensitivity.